Ocular palsies of obscure origin in South East Asia. Issue 6 (June 1974) - Tay, C. H.; Tan, Y. T.; Cheah, J. S.; Ransome, G. A.
Abstract : The clinical and laboratory findings are presented of 14 patients who were recently found to have an obscure form of ocular palsy during a three year study in Singapore. The disease, which has no predilection for any age groups, races, occupations, or sex, often manifests with acute onset of unilateral or bilateral cranial nerve paralysis involving the 3rd, 4th, 6th, first two branches of the 5th, and sometimes, the 2nd cranial nerve in various combinations. Major symptoms were diplopia, ptosis, giddiness, headache, facial numbness, proptosis, retro-orbital pain, chemosis, conjunctival irritation, blurred vision, and/or progressive blindness. Systemic complications were rare. Except for a raised erythrocyte sedimentation rate during the acute phase, exhaustive investigations—but short of a surgical exploration—were essentially noncontributory. All cleared up within two to four weeks, nine patients had spontaneous remission, while five improved only after a course of systemic corticosteroids. Two cases were left with some residual neurological deficits and one in this series had a relapse two years later. The relationship of this condition to those described outside South East Asia is discussed.